ANALYSIS OF NITRATE CONCENTRATION, PHOSPHATE AND SILICATE RELATIONSHIP WITH THE ABUNDANCE OF PLANKTONIC DIATOMS IN MERAL WATERS, KARIMUN DISTRICT - Rozalina, Rozalina; Nedi, Syahril; Nurrachmi, Irvina (Asian Journal of Aquatic Sciences, 2020)
Input of nutrients into the waters from various human activities (residential and industry) has the potential to cause changes in the physical, chemical and biological conditions of the waters. The study aims to determine the relationship of concentrations of nitrate, phosphate and silicate with the abundance of diatoms in the Meral waters. The method used is the survey method, the determination of the location of sampling is done by purposive sampling, data analysis (multiple regression). Based in the results of laboratory analysis nitrate concentrations ranged from 0,033 – 0,051mg/l, the phosphate concentration ranged from 0,076 – 0,086 mg/l, and silicate concentration ranged from 0,043 – 0,052 mg/l. The abundance of diatoms in Tanjung Tiram waters ranged from 90,3 – 208,3 ind/l. The results of statistical analysis of the relationship of nitrate, phosphate and silicate with the abundance of diatoms are expressed in terms of equation y = 58,460 + 904,562Nitrate – 251,562phosphate + 1573,489Silicate. This statement explains the concentration of nitrate, silicate positive (+) to the abundance of diatoms and phosphate related negative (-) to the abundance of diatoms. This condition shows that the nutrient concentration in these waters is relatively high so that it affects the abundance of diatoms.